The Role Of Production Factors On Tilapia Farming Business In Toba Samosir District - Marisa, Julia; Sitepu, Sukma Aditya (Journal of Saintech Transfer, 2019)
Tilapia farming system is a business system consisting of components that are interrelated to the farming of tilapia. Tilapia farmers in Toba Samosir Regency do not consider spending on factors of their business production so that the capital spent becomes large and influences the income of farmers. The purpose of community service implementation is to conduct an introduction to the factor analysis of tilapia business production so that farmers can do business efficiency and increase their income. The result of community service is that farmers start to analyze which factors of production need to be increased to increase income and factors that need to be reduced to reduce expenditure so that tilapia fish business income increases.